Long‐term safety and efficacy of tenofovir disoproxil fumarate substitution for hepatitis B immunoglobulin following liver transplantation. Issue 6 (19th September 2018) - Vasudevan, Abhinav; Ardalan, Zaid S; Ahmed, Navera; Apostolov, Ross; Gow, Paul J; Testro, Adam G; Gane, Ed J; Angus, Peter W
Abstract : Background and Aims: Limitations to the use of long‐term Hepatitis B Immunoglobulin (HBIg) following liver transplantation for hepatitis B (HBV) have led to the substitution of HBIg with oral nucleo(s)tide analogue prophylaxis. We prospectively assessed the long‐term safety and efficacy of switching to tenofovir disoproxil fumarate (TDF) from HBIg. Methods: An open‐label, multicenter switch study was conducted to evaluate the substitution of TDF for HBIg whilst continuing lamivudine (LAM) therapy in preventing the recurrence of HBV in patients who had been maintained as hepatitis B surface antigen (HBsAg)‐negative posttransplantation for at least 12 months. Results: Eighteen patients were enrolled (median age 66 years, range 42–78 years); 84% were male, and 78% on calcineurin inhibitors. Median time after transplantation was 14 years (range 5–19), and median duration of HBIg/LAM prior to the switch was 10 years (range 1–14). Median follow‐up was 5 years (range 5–8). Of 18 patients, 16 (89%) remained HBsAg and HBV DNA negative at the end of follow‐up. Two patients had re‐emergence of HBsAg without a detectable HBV DNA and no clinical sequelae. Creatinine clearance significantly reduced (median 59 mL/min to 51 mL/min, P = 0.03), necessitating dose reduction of TDF in six (33%) participants, with two eventually ceasing TDF. One patient switched back to HBIg by choice. All patients who changed therapy maintained an undetectable HBsAg. Conclusion: Substitution of HBIg with TDF in patients on LAM is well tolerated and effective for the long‐term prevention of HBV recurrence posttransplantation. Renal dysfunction occurs frequently in the posttransplant setting and can require dose adjustment of TDF or change of therapy. Abstract : Substitution of hepatitis B immunoglobulin with tenofovir disoproxil fumarate is well‐tolerated and effective for long‐term prevention of hepatitis B recurrence following liver transplantation. Renal dysfunction occurs frequently in the post‐transplant setting and can require dose adjustment of tenofovir or change of therapy.